2020
DOI: 10.1007/s00466-020-01821-5
|View full text |Cite
|
Sign up to set email alerts
|

Isogeometric analysis of thin Reissner–Mindlin shells: locking phenomena and B-bar method

Abstract: We propose a local type of B-bar formulation, addressing locking in degenerated Reissner-Mindlin plate and shell formulations in the context of isogeometric analysis. Parasitic strain components are projected onto the physical space locally, i.e. at the element level, using a least-squares approach.The formulation allows the flexible utilization of basis functions of different order as the projection bases. The present formulation is much cheaper computationally than the classicalB method. We show the numerica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(4 citation statements)
references
References 52 publications
0
4
0
Order By: Relevance
“…The researchers have shown that the problem can be solved or alleviated by using higher-order finite-element methods or adding special locking treatments to lower-order methods. The typical locking treatment approaches, which may not be restricted to solid-shell elements, include assumed natural strains (ANS), 18,19 enhanced assumed strain (EAS), 20 discrete strain gap (DSG), 21 B-method, [22][23][24][25] mixed formulations, 22,[26][27][28] selective/reduced integration, 26,[29][30][31] and projection techniques based on the moving least square (MLS). 32 Extensive literatures have reported that shells are studied by kinds of numerical methods: the finite element method (FEM), [33][34][35] the meshfree method, [36][37][38][39] and analytical 40,41 or semianalytical 42,43 methods and so forth.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The researchers have shown that the problem can be solved or alleviated by using higher-order finite-element methods or adding special locking treatments to lower-order methods. The typical locking treatment approaches, which may not be restricted to solid-shell elements, include assumed natural strains (ANS), 18,19 enhanced assumed strain (EAS), 20 discrete strain gap (DSG), 21 B-method, [22][23][24][25] mixed formulations, 22,[26][27][28] selective/reduced integration, 26,[29][30][31] and projection techniques based on the moving least square (MLS). 32 Extensive literatures have reported that shells are studied by kinds of numerical methods: the finite element method (FEM), [33][34][35] the meshfree method, [36][37][38][39] and analytical 40,41 or semianalytical 42,43 methods and so forth.…”
Section: Introductionmentioning
confidence: 99%
“…The researchers have shown that the problem can be solved or alleviated by using higher‐order finite‐element methods or adding special locking treatments to lower‐order methods. The typical locking treatment approaches, which may not be restricted to solid‐shell elements, include assumed natural strains (ANS), 18,19 enhanced assumed strain (EAS), 20 discrete strain gap (DSG), 21 trueB‐method, 22–25 mixed formulations, 22,26–28 selective/reduced integration, 26,29–31 and projection techniques based on the moving least square (MLS) 32 …”
Section: Introductionmentioning
confidence: 99%
“…There the local variables are directly interpolated with local B-spline functions without a Bézier projection and transformation to the Bernstein basis. Local B formulations where the locking strains or stresses are projected onto interpolation spaces with the lowest possible order for each element leading to different projection spaces for the inner, corner and boundary elements are presented in Hu et al [40,41]. Antolin et al [42,43] used discontinuous polynomial spaces for the projection of the strains.…”
Section: Introductionmentioning
confidence: 99%
“…In boundary element method (BEM), this translates into the ability to solve directly from the field variables at the control points defining the geometry [78,77,74,59,10,60,58,68]. In FEM, a 3D parameterization of the volume is still necessary [87,88], except when solving shell-like problems [53,13,14,38,49]. The present paper focuses on two following issues.…”
mentioning
confidence: 99%